2017
DOI: 10.1002/anie.201707019
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Cu/Pd Catalysis for Enantioselective Allylic Alkylation of Aldimine Esters: Access to α,α‐Disubstituted α‐Amino Acids

Abstract: An unprecedented enantioselective allylic alkylation of readily available aldimine esters has been developed, and is catalyzed by a synergistic Cu/Pd catalyst system. This strategy provides facile access to nonproteinogenic α,α-disubstituted α-amino acids in high yield with excellent enantioselectivity. The more challenging double allylic alkylation of glycinate-derived imine esters was also realized. Furthermore, this methodology was applied for the construction of the key intermediate of PLG peptidomimetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(54 citation statements)
references
References 75 publications
1
53
0
Order By: Relevance
“…Different from zhang's work,, we found that the easily‐accessible Pd(PPh 3 ) 4 was an efficient catalyst for the generation of the key π‐allylpalladium intermediate while the stereoselectivity could be controlled solely by the chiral copper catalyst. Results were further supported by the 31 P NMR experiments that the ligand scrambling was negligible in our bimetallic catalytic system . Nevertheless, the most significant challenge of using this practical Cu/Pd system is the application on glycine aldimine esters for the synthesis of α‐allyl α‐amino acids, as we found only the geminal‐allylation product was obtained even at low temperature (Table , entry 1).…”
Section: Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…Different from zhang's work,, we found that the easily‐accessible Pd(PPh 3 ) 4 was an efficient catalyst for the generation of the key π‐allylpalladium intermediate while the stereoselectivity could be controlled solely by the chiral copper catalyst. Results were further supported by the 31 P NMR experiments that the ligand scrambling was negligible in our bimetallic catalytic system . Nevertheless, the most significant challenge of using this practical Cu/Pd system is the application on glycine aldimine esters for the synthesis of α‐allyl α‐amino acids, as we found only the geminal‐allylation product was obtained even at low temperature (Table , entry 1).…”
Section: Methodssupporting
confidence: 70%
“…It should be noted that a same chiral ligand for both copper and palladium catalysts is essential in their protocols to minimize the undesired ligand scrambling and improve the stereoselectivity (Scheme ‐b). Concurrently, another synergistic Cu/Pd catalyzed AAA reaction of α‐substituted aldimine esters with broad substrate scope and excellent stereoselectivities was reported by our group . Different from zhang's work,, we found that the easily‐accessible Pd(PPh 3 ) 4 was an efficient catalyst for the generation of the key π‐allylpalladium intermediate while the stereoselectivity could be controlled solely by the chiral copper catalyst.…”
Section: Methodsmentioning
confidence: 53%
“…Almost simultaneously, Wang and co‐workers independently described a similar reaction through the combined use of a chiral Cu I complex and an achiral Pd 0 complex (Scheme ) . Control experiments from the research groups of Zhang and Wang suggest that: 1) the palladium catalyst is incapable of promoting the formation of the azomethine ylide as a nucleophile, and the palladium catalyst is indispensable for the formation of π‐allylpalladium; 2) the chiral copper complex seems to be responsible for its high enantioselectivity; 3) the Cu and Pd complexes activate the reaction in a synergistic manner.…”
Section: Synergistic Cu‐enolate and Pd Catalysismentioning
confidence: 99%
“…[20] Noticeably, each chiral ligand binding to a specific metal center generates highly reactive metalligand complexes through bimetallic catalysis. [21] Therefore, both nucleophiles and electrophiles can be activated independently by each individual catalyst in a concerted manner, consequently providing extra opportunities for enantiocontrol of the propargylic alkylation. Herein, we demonstrate the compatibility of these two distinct chiral metal complexes and describe the development of a highly flexible and reliable Ni/ Cu bimetallic catalytic system to deliver the corresponding aquaternary propargylated amino esters with excellent regioand enantioselectivity.…”
mentioning
confidence: 99%
“…Moreover, a lower yield was observed in the absence of Cs 2 CO 3 (entry 9 vs. 18). We found that the yield of 3 a was highly dependent on the protecting group of the propargylic alcohol, and no noticeable influence was observed on the enantioselectivity of the transformation (entries [19][20][21].…”
mentioning
confidence: 99%